Advanced Aspects of Spectroscopy - Muhammad Akhyar Farrukh (IntechOpen, 2012)
Spectroscopy is the study of absorption and emission of electromagnetic radiation due to the interaction between matter and energy that energy depends on the specific wavelength of electromagnetic radiation. This field has proven invaluable research tool in a number of areas including chemistry, physics, biology, medicine and ecology. The spectroscopic field of research is growing day-by-day and scientists are exploring new areas in this field by introducing new techniques. The main purpose of this book is to highlight these new spectroscopic techniques like Magnetic Induction Spectroscopy, Laser-Induced Breakdown Spectroscopy, X-ray Photoelectron Spectroscopy, Low Energy Electron Loss Spectroscopy, Micro- to Macro-Raman Spectroscopy, Liquid-Immersion Raman Spectroscopy, High-Resolution Magic Angle Spinning (HR-MAS) Nuclear Magnetic Resonance (NMR) Spectroscopy, Injection and Optical Spectroscopy, and Nano Spectroscopy. This book is divided into five sections including General Spectroscopy, Advanced Spectroscopy, Nano Spectroscopy, Organic Spectroscopy, and Physical Spectroscopy which cover topics from basic to advanced levels which will provide a good source of learning for teaching and research purposes.
English
Keywords: Physical Sciences; Engineering and Technology; Optoelectronics; Physics; Optics and Lasers